РЕЛИКТОВЫЙ СУБАЭРАЛЬНЫЙ РЕЛЬЕФ ПОД ВОДАМИ МИРОВОГО ОКЕАНА - Лукьянова С.А. (My University, 2003)
Numerous examples from various regions (easterm margin of the USA, Puerto-Rico, south-east of Africa, arctic shelf, continental margins of Israel and Bulgaria) illustrate influence of originally subaerial relict landforms of various origin on sediment transport over the shelf. Submerged river valley mostly make obstacles to longshore sediment transport, while relict coastal forms, such as beach ridges and dunes, impede transversal sediment flows.
Keywords: 551.462:551.4.072